PERTUMBUHAN DAN PERKEMBANGAN SAWO KECIK (Manilkara kauki (L.) Dubard), GEBANG (Corypha utan Lamk.), PULAI (Alstonia scholaris R.Br), DAN VITEX (Vitex pubescens Vahl.) SELAMA MENGALAMI KEKERINGAN - , NUR RAHMAWATI W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recent climate change has been difficult to be avoided. Besides, it impacts on life, one of them is drought. In order to maintain the vegetation found in the dry areas, people need to look for the alternative plants that resist from the drought stress. Some species with potential adaptation to drought are Sawo kecik (Manilkara kauki (L.) Dubard), Gebang (Corypha utan Lamk.), Pulai (Alstonia scholaris R.Br), and Vitex (Vitex pubescent Vahl.). The purpose of this reseach was to examine the growth and development of palnts, the morfhological, physiological, and anatomical responses of these plants in drought condition. Drought stress treatment was applied for 10 days, 20 days, 30 days, and 40 days, whereas control plants were watered every 2 days. Each treatment used 3 replication. Parameters observed were plant height, stem diameter, leaf area, number of leaves, transpiration rate, stomatal index, proline levels, plant water content, total dry weight, root dry weight, and the anatomy of stem, root, and leaves. Physiological data obtain were analized by t test. The result of this reseach indicated that plant responded to the drought stress by increasing level of proline, leaf xylem thickness, root cortex thickness, stem xylem thickness and root epidermis thickness. Drought stress responses also indicated by decreasing its plant height, stem diameter, leaf area, number of leaves, transpiration rate, stomatal index, water content, plant dry weight, root dry weight, mesophyll thickness, leaves phloem thickness and stem phloem thickness. Gebang is the most adaptive plants to drought stress compared with other.